2009
DOI: 10.1002/pros.21042
|View full text |Cite
|
Sign up to set email alerts
|

From pathogenesis to prevention of castration resistant prostate cancer

Abstract: CRPCa is the end-stage of a multifactorial and heterogeneous disease process. Pathogenetic factors responsible for the development of the CRPCa phenotype are detectable in the patient's PCa tissue long before the clinical onset of the disease. This approach provides opportunity for early detection and prevention by targeting pathways relevant for the individual disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 63 publications
0
57
0
Order By: Relevance
“…Generally, it has been reported that the AR is expressed in nearly all types of cancers of the prostate, before and after androgen ablation therapy (11). The high levels of AR expression and the development of hypersensitive receptors have been recognized as a feature associated with the development of CRPC (13,16). Hobisch et al (17) showed that metastases from PCa expressed the AR following endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it has been reported that the AR is expressed in nearly all types of cancers of the prostate, before and after androgen ablation therapy (11). The high levels of AR expression and the development of hypersensitive receptors have been recognized as a feature associated with the development of CRPC (13,16). Hobisch et al (17) showed that metastases from PCa expressed the AR following endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 This notion is supported by the observation that the proliferation index of cancer cells surrounding NE cells is higher than that of distal cancer cells. 30,31 Pathogenetic factors responsible for the development of the androgen-resistant phenotype are detectable in PC tissues long before the clinical onset of the disease 32 but usually escape clinical detection and attention. Some authors have found that the acquisition of NE characteristics is fully reversible, 20 thus early detection and prevention of castration resistant PC may provide a new strategy to improve survival of patients diagnosed with PC at risk to fail standard androgen deprivation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…3; Taplin and Balk 2004;Attard et al 2009a;Bonkhoff and Berges 2010). Notably, castration-resistant tumors express AR as well as AR target genes such as PSA, indicating that pathway activity is intact (Gregory et al 1998).…”
Section: Retention Of Ar Signaling In Castration Resistancementioning
confidence: 99%